Nonomuraea indica sp nov., novel actinomycetes isolated from lime-stone open pit mine, India - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Li, Jie; Nie, Guo-Xing; Tang, Shu-Kun; Al Ruwaili, Jamal; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (Journal of Antibiotics, 2015)
A Gram-positive, aerobic, nonmotile actinomycete strain designated DRQ-2(T) was isolated from the soil sample collected from limestone open pit mine from the Gulbarga region, Karnataka province, India. Strain DRQ-2(T) was identified as a member of the genus Nonomuraea by a polyphasic approach. Strain DRQ-2(T) could be differentiated from other members of the genus Nonomuraea on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain DRQ-2(T) showed highest sequence similarity to Nonomuraea muscovyensis DSM 45913(T) (99.1%), N. salmonea DSM 43678(T) (98.2%) and N. maheshkhaliensis JCM 13929(T) with 98.0%, respectively. Chemotaxonomic properties showing predominant menaquinones of MK-9 (H-4), MK-9(H-2) and MK-9(H-6), major polar lipids comprised diphosphatidylglycerol, phosphatidylmono methyl ethanolamine (PME), phosphatidylethanolamine (PE), hydroxy-PME (OH-PME), hydroxy PE (OH-PEE), phosphatidylglycerol (PG), ninhydrin-positive phosphoglycolipid and unknown phospholipid, fatty acids with major amounts of i-C-16:0, ai-C-15:0 and ai-C-17:0 supported allocation of the strain to the genus Nonomuraea. Results of DNA-DNA hybridization and physiological tests allowed genotypic and phenotypic differentiation of strain DRQ-2(T) from closely related species. The genomic DNA G+C content of the organism was 72.5 mol%. On the basis of phenotypic, chemotypic and molecular characteristics, strain DRQ-2(T) represents a novel species of the genus Nonomuraea, for which the name N. indica sp. nov. is proposed, with type strain DRQ-2(T) (= NCIM 5480(T) = CCTCC AA 209050(T)).

Actinorectispora indica gen. nov., sp nov isolated from soil, a member of the family pseudonocardiaceae - Quadri, Syed Raziuddin; Tian, Xin-Peng; Zhang, Jing; Al Ruwaili, Jamal; Hozzein, Wael N.; Agsar, Dayanand; Li, Wen-Jun; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2016)
The taxonomic positions of three Gram-stain-positive, aerobic strains, designated YIM 75722, 75726 and 75728(T), and isolated from a soil sample collected from Kurnool of Andhra Pradesh province, India, were assessed using a polyphasic approach. Growth was observed at pH 7.0-10.0 (optimum pH 7.0), 15-28 degrees C (optimum 28 degrees C) and 0-8% (w/v) NaCl (grew without NaCl). Strains showed cylindrical spores with straight-chain morphology on aerial mycelium, but did not reveal sporangium-like structures or fragmentation of the substrate mycelium. Whole-cell hydrolysates of all strains contained galactose and ribose as the diagnostic sugars and meso-diaminopimelic acid as the diamino acid. The predominant menaquinone was MK-9(H-4); MK-9 (H-6) and MK-10 (H-4) were present in smaller amounts. The phospholipid pattern consisted mainly of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylcholine. The major fatty acids were i-C-15: 0, ai-C-15: 0, i-C-17 : 0 and ai-C-17 : 0. The genomic DNA G+C content was 68.0 mol%. Phylogenetic analysis, based on 16S rRNA gene sequences, revealed that strain YIM 75728(T) should be placed within the family Pseudonocardiaceae, in which the strain formed a distinct lineage. The combination of phylogenetic analysis, phenotypic characteristics and chemotaxonomic data support the conclusion that strain YIM 75728(T) represents a novel species of a novel genus of the family Pseudonocardiaceae for which the name Actinorectispora indica gen. nov., sp. nov., is proposed. Strain YIM 75728(T) (=DSM 45410(T)=CCTCC AA 209065(T)) is the type strain of Actinorectispora indica. Strain YIM 75728(T) was considered as the type strain over the other two strains based on the highest sequence read length of the strain.